THE INFLUENCE OF CORPORATE SOCIAL RESPONSIBILITY (CSR) AND GOOD CORPORATE GOVERNANCE (GCG) ON COMPANY VALUE WITH FINANCIAL PERFORMANCE AS AN INTERVENING VARIABLE - Ningtyas, Dinur Aulia Putri; Rusmawati, Zeni; Maharani, Rieska (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
This research aims to determine the influence of Corporate Social Responsibility (CSR) and Good Corporate Governance (GCG) on company value with financial performance as an intervening variable. CSR variables are measured using CSRI published by GRI G4, GCG variables are measured by audit committee, independent commissioner, managerial ownership and institutional ownership. The financial performance variable is measured using return on equity (ROE) while the firm value variable is measured using Tobins'Q . The type of research used in this research is quantitative research using panel data and analyzed using SPSS Version 25 software. This research uses a purposive sampling technique with the object being raw materials sector companies listed on the Indonesia Stock Exchange (BEI) in 2017-2022. The number of samples obtained was 99 samples. Because the data used was not normally distributed, data outliers were carried out by removing 9 data so that the remaining 90 data would be used as samples. The results of this research indicate that Corporate Social Responsibility (CSR) has no effect on financial performance. Good Corporate Governance (GCG) has no effect on financial performance. Corporate Social Responsibility (CSR) influences company values. Good Corporate Governance (GCG) has no effect on company value. Financial Performance has no effect on company value, Financial Performance cannot mediate CSR on Company Value. Financial Performance can mediate GCG on Company Value.